Remediation and Local Globalizations: How Taiwan's “Digital Video Knights-Errant Puppetry” Writes the History of the New Media in Chinese. - Silvio, Teri (Cultural Anthropology, 2007)
This article analyzes the Pili International Multimedia Company's digital video knights-errant puppetry" serials, a popular culture genre unique to Taiwan, to answer two questions. First, how do digital technologies, originally developed to meet the needs of the American military and entertainment industries, become embedded in a different cultural context? Second, how does this embedding allow media technologies to become something through which distinctly local models of globalization itself may be imagined? Analyzing both the style of the serials and the discourse of producers and fans, I argue that new media technologies, despite their foreign origins, may not only be adapted or resisted, but may also come to be imagined as emerging from local aesthetics and local needs. Through the specific ways they utilize both digital and traditional technologies, the Pili producers and fans construct a utopian vision of what globalization might look like if Taiwan were at the center. Reprinted by permission of the publisher.